2011
DOI: 10.1093/ejechocard/jer071
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular systolic performance is improved in elite athletes

Abstract: Elite athletes show a significant shortening of the systolic time duration in comparison with sedentary controls, in association with a significant increase in LV emptying velocity. This pattern characterizes the physiological LV adaptation of the athletes and may potentially be useful in differential diagnosis of the 'athlete heart'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…A final total of 23 studies met our inclusion criteria, 7, with athletes directly compared with controls in 13 studies. 7,18,[20][21][22][23]27,29,33,35,36,38,39 The identified studies included 19 cross-sectional and 4 longitudinal studies conducted in Europe (n=14), the United States (n=6), Africa (n=2), and Iran (n=1). Across the studies, aortic root dimensions were reported in 5580 unique elite athletes comprised of 1506 endurance-trained athletes, 425 strength-trained athletes, 213 combined endurance-and strength-trained athletes, and a heterogeneous group of 3436 athletes with mixed training.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A final total of 23 studies met our inclusion criteria, 7, with athletes directly compared with controls in 13 studies. 7,18,[20][21][22][23]27,29,33,35,36,38,39 The identified studies included 19 cross-sectional and 4 longitudinal studies conducted in Europe (n=14), the United States (n=6), Africa (n=2), and Iran (n=1). Across the studies, aortic root dimensions were reported in 5580 unique elite athletes comprised of 1506 endurance-trained athletes, 425 strength-trained athletes, 213 combined endurance-and strength-trained athletes, and a heterogeneous group of 3436 athletes with mixed training.…”
Section: Resultsmentioning
confidence: 99%
“…Aortic root was measured at the aortic valve annulus in 15 studies 7,[18][19][20][23][24][25]27,28,30,31,34,36,38,39 and at the sinuses of Valsalva in 12 studies. 7,[21][22][23][24]26,28,29,32,33,35,37 (Tables 1 and 2). In the 13 studies that directly compared athletes with controls, there were variations in the degree of matching; 11 studies matched for age, and 3 studies explicitly stated that they matched for body size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We classified the athletes' sports disciplines into four subgroups according to the predominant characteristics of exercise training: (1) skill (i.e., primarily technical activities; n = 226), including golf, table tennis, equestrian, gymnastics, shooting, fencing, karate, taekwondo, and sailing; (2) power activities (i.e., primarily isometric activities; n = 177), including weightlifting, wrestling, and short-distance running (100-200 m); (3) mixed disciplines (i.e., disciplines with alternate isometric and isotonic components; n = 339), including soccer, basketball, volleyball, handball, water polo, and tennis; and (4) endurance disciplines (e.g., primarily isotonic activities; n = 403), including rowing, canoeing, swimming, longdistance running and marathon, cycling, triathlon, and pentathlon. [25][26][27][28] The athletes were compared with a group of 154 healthy sedentary subjects. They were volunteers, selected on the basis of similar age (range, 18-40 years) and gender proportion (86 men [56%]) and were either completely sedentary or engaged in <3 hours of exercise per week, and none was involved in sports competitions.…”
mentioning
confidence: 99%
“…Caselli et al 46 , en un estudio realizado en 429 atletas que participaban en disciplinas de habilidad, potencia, resistencia aeróbica o mixtas, encontraron que los atletas de resistencia aeróbica tenían mayor volumen de fin de diástole y de fin de sístole del ventrículo izquierdo, un incremento en el espesor de la pared del ventrículo izquierdo, mayor velocidad de flujo sistólico y mayor volumen latido comparado con los deportistas de las demás disciplinas. Dichos hallazgos corroboran nuestros resultados, debido a que los futbolistas clasificados como «resistentes» presentaron ante el estrés ortostático un mayor índice de eyección, índice de contractilidad, índice de aceleración e índice del volumen de final de diástole en comparación con los «potentes».…”
Section: Discussionunclassified